568. THE PROGNOSTIC EFFECT OF PATHOLOGICAL LYMPH NODE REGRESSION AFTER NEOADJUVANT CHEMOTHERAPY FOR OESOPHAGEAL ADENOCARCINOMA – A MULTICENTRE STUDY. (24th September 2022) - Moore, Jonathan; Green, Michael; Van Hemelrijck, Mieke; Deere, Harriet; Evans, Richard PT; Elshafie, Mona; Lavery, Anita; McGuigan, Andrew; Douglas, Rosalie; Mcmanus, Damian; Horne, Joanne; Walker, Robert; et al.
Abstract: The prognostic benefit of primary tumour and lymph node (LN) downstaging after neoadjuvant chemotherapy for oesophageal adenocarcinoma (OAC) is well described. However, there is no robust evidence regarding the prognostic effect of pathological LN regression despite emerging evidence of a discrepancy, in some patients, between tumour regression grade in the primary tumour and response in regional LNs. The aim of this study was to investigate the relationship between pathological LN regression, tumour recurrence and survival. Retrospective, multicentre cohort study including 763 patients with OAC treated with neoadjuvant chemotherapy followed by surgery at 5 high-volume tertiary referral centres in the United Kingdom. Tumour regression was assessed in the primary tumour (Mandard) and LNs retrieved from oesophagectomy specimens. Patients were classified as LN negative (no evidence of tumour or regression in any LN), complete LN-responders (evidence of regression ≥1 LN, no residual tumour in any LN), partial LN-responders (evidence of regression ≥1 LN with residual tumour ≥1 LN) and LN non-responders (no or minimal regression in any LN). Survival analysis was performed using Kaplan-Meier and Cox regression. Overall, 243 (31.8%) patients were classified as LN negative, 62 (8.1%) as complete LN-responders, 155 (20.3%) as partial LN-responders and 303 (39.7%) as LN non-responders. Some patients had a LN response in the absence of a response in the primary tumour (97/431, 22.5%). Multivariable Cox regression survival analysis (adjusting for age, gender, chemotherapy regimen, clinical stage, tumour grade, lympho-vascular invasion and primary tumour response) demonstrated improved overall survival in complete LN-responders (Hazard ratio (HR) 0.37 95% confidence interval (CI) 0.24-0.58), partial LN-responders (HR 0.70 95% CI 0.55-0.89) and LN negative patients (HR 0.34 95% CI 0.26-0.44) compared to LN non-responders. In this cohort of patients with OAC treated with neoadjuvant chemotherapy prior to surgical resection, LN regression was a strong prognostic factor independent of primary tumour response, which was discordant in a significant number of patients. Complete LN-responders had equivalent survival to those with negative LN. Complete and partial LN-responders had better survival than LN non-responders. Evaluation and documentation of LN regression should be considered during the standard pathological reporting of oesophagectomy specimens.